Causal effects of gut microbiota on diabetic neuropathy: a two-sample Mendelian randomization study - Xu, Ming; Hao, Jinxuan; Qi, Yijie; Wu, Baofeng; Li, Ru; Yang, Xifeng; Zhang, Yi; Liu, Yunfeng (Frontiers in Endocrinology, 2024)
Objective: Previous observational studies have suggested an association between gut microbiota and diabetic neuropathy (DN). However, confounding factors and reverse causality make the causal relationship between gut microbiota and DN uncertain. We aimed to investigate the interactive causal relationships between the abundance of gut microbiota and DN.Methods: We conducted a Mendelian randomization (MR) analysis to examine the causal relationship between gut microbiota and DN. Genomic data on gut microbiota at the genus level were obtained from the MiBioGen Consortium, including 18,340 individuals of European descent. Data on diabetic polyneuropathy (DPN) were obtained from the FinnGen Consortium, which included 1,048 cases and 374,434 controls, while data on diabetic autonomic neuropathy (DAN) were also obtained from the FinnGen Consortium, including 111 cases and 374,434 controls. Causal effects were primarily estimated using inverse variance weighted (IVW) analysis, supplemented with four validation methods, and additional sensitivity analyses to assess the pleiotropy, heterogeneity, and robustness of instrumental variables.Results: The IVW analysis indicated that Prevotella 9 had a protective effect on DPN (OR = 0.715, 95% CI: 0.521-0.982, P = 0.038), and Bacteroides also showed a protective effect (OR = 0.602, 95% CI: 0.364-0.996, P = 0.048). On the other hand, Ruminococcus 2 had a promoting effect on DPN (OR = 1.449, 95% CI: 1.008-2.083, P = 0.045). Blautia (OR = 0.161, 95% CI: 0.035-0.733, P = 0.018), Clostridium innocuum group (OR = 3.033, 95% CI: 1.379-6.672, P = 0.006), and Howardella (OR = 2.595, 95% CI: 1.074-6.269, P = 0.034) were causally associated with DAN in the IVW analysis, with no evidence of heterogeneity or pleiotropy. Sensitivity analyses showed no significant pleiotropy or heterogeneity.Our study identified a causal relationship between gut microbiota and the increased or decreased risk of diabetic neuropathy. These findings underscore the importance of adopting a comprehensive approach that combines gut microbiota modulation with other therapeutic interventions in the management of diabetic neuropathy.